(untitled) (International relations and international law Journal, 2016)
This article comprehensively considered Japan’s policy in Central Asia. Japan does not hide their interest in the natural resources of Central Asia, and over the years will give the opportunity to understand the basis of their interests. In this regard, the establishment of relations with each state completely depended on their resource capabilities. Financial support has been established within the framework of assistance for the development of this sector. At first glance it seems that Japan’s policy in the region is seen without perspective, because of its remoteness. However, analyzing the doctrine, concepts and initiatives of Japan, we can confidently assert that its policy in the region is not temporary, and have long-term. In the history of Japan’s diplomacy was never limited by «one-time actions,» and its policy is constantly focused on long-term.